Comparative Cytogenetics and Neo-Y Formation in Small-Sized Fish Species of the Genus Pyrrhulina (Characiformes, Lebiasinidae) - de Moraes, Renata Luiza Rosa; Sember, Alexandr; Bertollo, Luiz Antônio Carlos; de Oliveira, Ezequiel Aguiar; Ráb, Petr; Hatanaka, Terumi; Marinho, Manoela Maria Ferreira; Liehr, Thomas; Al-Rikabi, Ahmed B. H.; Feldberg, Eliana; Viana, Patrik F.; Cioffi, Marcelo de Bello (Frontiers in Genetics, 2019)
Although fishes have traditionally been the subject of comparative evolutionary studies, few studies have focused in the application of multipronged modern molecular cytogenetic techniques (such as comparative genomic hybridization = CGH and whole chromosome painting = WCP) to in deeper analyze the karyotype evolution of specific groups, especially historically neglected small-sized ones. Representatives of the family Lebiasinidae (Characiformes) are a representative example, where only a few cytogenetic studies conducted thus far. Here, we aim to elucidate the evolutionary processes behind the karyotype differentiation of Pyrrhulina species based on a finer-scale cytogenetic level. To achieve this, we applied C-banding, repetitive DNA mapping, CGH and WCP in P. semifasciata and P. brevis. Our results showed 2n = 42 in both sexes of P. brevis, while the difference in 2n between male and female in P. semifasciata (♂41/♀42) stands out due to the presence of multiple X1X2Y sex chromosome system, until now unique for this family. As a remarkable common feature, multiple 18S and 5S rDNA sites are present, with occasional synteny or tandem-repeat amplification. Male-vs.-female CGH experiments in P. semifasciata highlighted the accumulation of male-enriched repetitive sequences in the pericentromeric region of the Y chromosome. Inter-specific CGH experiments evidenced divergences between both species genomes based on the presence of several species-specific signals, highlighting their inner genomic diversity. WCP with the P. semifasciata-derived Y (PSEMI-Y) painted not only the entire metacentric Y chromosome in males but also the X1 and X2 chromosomes in both male and female chromosomes of P. semifasciata. In cross-species experiments, the PSEMI-Y probe painted four acrocentric chromosomes in both males and females of the other tested Pyrrhulina species. In summary, our results show that both intra- and interchromosomal rearrangements together with dynamics of repetitive DNA significantly contributed to karyotype divergence of Pyrrhulina species, possibly promoted by specific populational and ecological traits and accompanied in one species by the origin of neo-sex chromosomes. The present results highlight how particular evolutionary scenarios found in fish species can help to clarify several issues related to genome organization and the karyotype evolution of vertebrates as a whole.